PENETRATION OF A SOUND FIELD THROUGH A MULTILAYERED SPHERICAL SHELL - G. Ch. Shushkevich; N. N. Kiselyova (Informatika)
An analytical solution of the boundary problem describing the process of penetration of thesound field of a spherical emitter located inside a thin unclosed spherical shell through a permeable multilayered spherical shell is considered. The influence of some parameters of the problem on the value of the sound field weakening (screening) coefficient is studied via a numerical simulation.